2013
DOI: 10.1016/j.ajic.2013.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Viral outbreaks in neonatal intensive care units: What we do not know

Abstract: Our analysis of the viral origins of nosocomial infections in NICUs can be a valuable tool in the investigation of neonatal infections. The mortality rates reported in this analysis demonstrate the significance of noncongenital viral infections in NICUs and the need for more effective outbreak prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 10 publications
0
52
0
3
Order By: Relevance
“…Biosecurity measures for the Cats Protection Adoption Centres are of a high standard across the country, as they all adhere to strict hygiene guidelines. However, it is known in human hospitals that viral diseases, particularly gastrointestinal pathogens, are not easily contained, with rotavirus being one of the most frequent pathogens to transmit nosocomially and cause outbreaks, particularly in pediatric and neonatal wards (30). A return to Truro 6 weeks later found a complete turnover of cats and a reduction of the center prevalence from 61.2% (21/34) to 2.5% (1/40), despite the continued influx of new individuals, which might be thought to maintain epidemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Biosecurity measures for the Cats Protection Adoption Centres are of a high standard across the country, as they all adhere to strict hygiene guidelines. However, it is known in human hospitals that viral diseases, particularly gastrointestinal pathogens, are not easily contained, with rotavirus being one of the most frequent pathogens to transmit nosocomially and cause outbreaks, particularly in pediatric and neonatal wards (30). A return to Truro 6 weeks later found a complete turnover of cats and a reduction of the center prevalence from 61.2% (21/34) to 2.5% (1/40), despite the continued influx of new individuals, which might be thought to maintain epidemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…The role of immature respiratory and immune systems has a critical impact on susceptibility to nosocomial infections and infection-related complications during the birth hospitalisation [33]. Although bacterial outbreak has long been the main focus of nosocomial infection during the neonatal period, previous studies have demonstrated that viral outbreaks can contribute to an equivalent level of mortality (6.4% vs. 7.17% respectively) [33,34].…”
Section: Viral Infection In Preterm Infants During the Birth Hospitalmentioning
confidence: 99%
“…Although bacterial outbreak has long been the main focus of nosocomial infection during the neonatal period, previous studies have demonstrated that viral outbreaks can contribute to an equivalent level of mortality (6.4% vs. 7.17% respectively) [33,34]. The role of viruses in nosocomial infection has become increasingly recognised, with several studies showing that 20 to 50% of very preterm infants, born at ≤ 32 weeks’ gestation, acquired a nosocomial infection with a respiratory virus during their birth hospitalisation, often in the absence of clinical indicators of respiratory illnesses [3537].…”
Section: Viral Infection In Preterm Infants During the Birth Hospitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates were similar in viral outbreaks compared with bacterial outbreaks. Out of the 48 patients who died in the above-referenced study, a respiratory viral cause was found in 89.6% of the cases [35]. Bennet et al [36] performed year-long surveillance on preterm neonates and showed that 52% tested positive for a respiratory virus during their birth hospitalization.…”
Section: Neonatesmentioning
confidence: 97%